The Effect of Contextual Interference on Static and Dynamic Balance in Mentally Retarded People - Hanieh Mohammadi; Shahzad Tahmasebi Boroujeni; Jamal Fazel Kalkhoran (University of Tehran, 2016)
The aim of the present study was to investigate the effect of contextual interference on balance of mentally retarded people. For this purpose, 40 educable and mentally retarded boys in Qazvin city (mean age 24.45 ± 3.120) were randomly divided into two groups: blocked and random practice. After the pretest, given their practice arrangement, subjects in each group performed their workout for 4 weeks (3 sessions per week) as the acquisition phase. Acquisition test was conducted in the last session, and then retention and transfer tests were performed after 48 hours. After Kolmogorov-Smirnov test verified normal data distribution and Leven test examined the homogeneity of variances, analysis of variance with repeated measures showed that the intervention was effective and the groups significantly improved (P=0.0005). The results of the independent t test (to compare two groups in static balance) showed that random practice group performed better in retention test (P=0.007) whereas no significant differences were observed between the groups in transfer test (P=0.061). In addition, dynamic balance results showed that random practice group performed better than the blocked practice group and it had a significant difference in retention and transfer tests (respectively P=0.001, P=0.002). So, mentally retarded people can use the beneficial effects of random practice.